Kepuasan Kerelasian: Model Evaluasi Partisipasi Mahasiswa dalam Pertemuan Layanan (Customer Education dan Interaction Quality) di Perguruan Tinggi Wilayah Cirebon - Sahara Sahara; Asep Gunawan (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
The purpose of this paper is to seek to examine the role of customer education (CE) and interaction quality (IQ) to the customer participation (CP) and its impact on customer relationship satisfaction (RS). Design methodology: The sample uses the respondent hospital patients in the disease amounted to 185 respondents. Structural equation modeling and confirmatory factor analysis were performed to evaluate the model hypotheses. Size reliability and validity were also examined. Findings: Statistical analysis shows that following each CE, and IQ have a positive impact on CP and CP increase RS. The practical implications: In the context of the service industry in higher education in the region III Cirebon, West Java, Indonesia, the study offers a deeper understanding of the factors that influence the CP, and how CP influences RS. This understanding will help practitioners formulate policies and effective marketing strategies and strengthening services to customers on the basis of an interactive service on the front lines. The concierge service at the core and at the forefront of service is able to improve customer satisfaction by providing high customer value. Originality: This paper uses a sample on education service in measuring customer interaction quality education and who have not previously been tested on previous studies.